Acting for biodiversity in a food value chain - Lappalainen, Otto; Kuhmonen, Irene; Teerikangas, Satu; Salo, Matti; Turunen, Marja (Elsevier, 2026)
Food production ranks among the primary causes of biodiversity decline. While drivers of this decline are relatively well known, the role of food value chains in contributing to efforts to mitigate the ongoing biodiversity decline remains poorly understood. Adopting a qualitative, grounded theory research design, we explore companies' biodiversity actions across a national food value chain. Empirically, we study 37 companies operating in the Finnish food value chain via interviews aiming to capture the companies' actions on biodiversity, supplemented by sustainability reports and websites. Our analysis identified a total of 161 actions across 20 categories. The actions were either geared at land use or they were undertaken in organizational functions. Land use related biodiversity actions aimed either at sharing productive land with biodiversity or sparing land for biodiversity via efficient land use practices, although improving soil and growing conditions could be seen as relating to both aims. Further, we observed that only actions that took place in primary production and that aimed at sharing land with nature and improving soil, had direct, positive impacts on biodiversity. In contrast, while land sparing strategies were commonly cited by value chain actors, the causal mechanism through which spared land could contribute to biodiversity conservation instead of prompting other forms of intensive land use, remained unidentified. Actions undertaken in organizational functions related to supply chain management, sales and marketing, and corporate-level actions, bearing indirectly on biodiversity. In closing, our findings call companies to move beyond strategic commitments to identify and support concrete land use actions beneficial to biodiversity.